2017
DOI: 10.1016/j.nicl.2016.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of cortical thickness and surface area in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder often associated with changes in cortical volume. The constituents of cortical volume – cortical thickness and surface area – have separable developmental trajectories and are related to different neurobiological processes. However, little is known about the developmental trajectories of cortical thickness and surface area in ASD. In this magnetic resonance imaging (MRI) study, we used an accelerated longitudinal design to investigate the cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 46 publications
6
64
1
Order By: Relevance
“…Regarding the developmental trajectories of CT in ASD, quadratic age trajectories composed of three phases have been proposed: accelerated expansion during early childhood; accelerated thinning during late childhood and adolescence; and, lastly, decelerated thinning during early adulthood . Notably, recent large‐sample studies have reported a dynamic CT pattern of group differences observed between children with ASD and those with TD over broad regions of the cortex, but with differences fading over adolescence to a virtually identical CT by young adult age . Furthermore, a multivariate classification study using the Autism Brain Imaging Data Exchange dataset concluded that anatomical differences in cortical measures of CV, CT, and surface area offer very limited diagnostic value in ASD .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the developmental trajectories of CT in ASD, quadratic age trajectories composed of three phases have been proposed: accelerated expansion during early childhood; accelerated thinning during late childhood and adolescence; and, lastly, decelerated thinning during early adulthood . Notably, recent large‐sample studies have reported a dynamic CT pattern of group differences observed between children with ASD and those with TD over broad regions of the cortex, but with differences fading over adolescence to a virtually identical CT by young adult age . Furthermore, a multivariate classification study using the Autism Brain Imaging Data Exchange dataset concluded that anatomical differences in cortical measures of CV, CT, and surface area offer very limited diagnostic value in ASD .…”
Section: Discussionmentioning
confidence: 99%
“…When examining cortical structure, surface‐based cortical matrices, such as cortical thickness (CT), fractal dimension (FD; a marker of cortical complexity), and sulcal depth (SD), are of particular interest. Unlike the conventional approach to examining regional gray matter volume, these surface‐based cortical measures focus on cortical folding . As they reflect different aspects of cortical architecture and stem from different genetic and cellular mechanisms in the brain, they have the potential to provide a more complete picture of the pathophysiology involved in the cortical architecture of ASD than gray matter volume.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased SA was also observed for younger children with ASD (Ohta et al, 2016), which is consistent with the findings of early overgrowth followed by accelerated decline in brain volumes (Hardan et al, 2009) and suggests that this can be a robust structural correlate of ASD. However, it is less clear on the developmental trajectory of SA with age, with one study reporting an accelerated reduction in SA with age (from 7 to 39 years) (Doyle‐Thomas et al, 2013b), while in a larger study (180 participants) the reduction in SA with age observed in healthy controls was not observed in ASD participants (Mensen et al, 2017).…”
Section: Structural Biomarkers Of Asdmentioning
confidence: 99%
“…Unlike the conventional approach to examine regional gray matter volume, these surface-based cortical measures focus on cortical folding. [7][8][9][10] Since they reflect different aspects of cortical architecture and stem from different genetic and cellular mechanisms in the brain, 11,12 they have the potential to provide a more complete picture of the pathophysiology involved in the cortical architecture of ASD than gray matter volume.…”
Section: Introductionmentioning
confidence: 99%